Metaphyseal anadysplasia with varus femurs and small kneecaps: a new variant of Metaphyseal anadysplasia type 1 in Czech siblings - Vážná, Anna; Mařík, I; Zemková, Daniela; Krulišová, Veronika; Vlčková, Zdeňka; Hrušková, Lucie; Paszeková, Helena; Michalovská, Renáta (Pohybové ústrojí. Pokroky ve výzkumu, diagnostice a terapii, 2021)
The authors present the clinical and radiological findings of two siblings in whom two previously unpublished heterozygous cis-variants (c.236T>G and c.251A>C ) in the MMP13 gene were identi- fied by genetic testing. We propose to use the name “Metaphyseal anadysplasia with varus femurs and small kneecaps” for this newly described variant of metaphyseal anadysplasia type 1.
Keywords: genua vara; Humans; Radiography; Patella; radiografie; Female; Siblings; vývojové onemocnění kostí; lidé; Lower Extremity Deformities, Congenital; sourozenci; femur; patela; předškolní dítě; Femur; ženské pohlaví; vrozené deformity dolní končetiny; Male; metafyzární anadysplazie; Czech Republic; Česká republika; mužské pohlaví; Child, Preschool; Genu Varum; Bone Diseases, Developmental